A Festschrift in Honor of Meredith Blackwell. (2nd January 2018) - Spatafora, Joseph; Aime, M. Catherine; Zhang, Ning; Seifert, Keith A.
ABSTRACT: The end of the 20 th century and the beginning of the 21 st will be remembered as the golden age of molecular systematics of Fungi. The development of the Polymerase Chain Reaction (PCR), automated sequencing, and explicit algorithms for inferring phylogenetic trees transformed fungal systematics into a hypothesis-testing discipline that would go on to serve as the foundation for comparative and evolutionary genomics. Many mycologists participated in this modernization of mycology and perhaps none more than Meredith Blackwell. She has played – and continues to play – a leadership role in transforming mycology into a modern science based on a robust understanding of organismal biology, development, testing and refinement of biologically meaningful hypotheses, and incorporation of emerging technologies to data collection and analysis. In this volume we recognize Meredith and her contributions to mycology with the publication of the first Festschrift issue in the 110 year history of Mycologia .